Learning Methods of Tahfizh Al-Qur'an in Improving the Quality of Memorization of Visually Impaired Santri in Islamic Boarding Schools - Ruslan Abdul Gani (Riviera Publishing, 2024)
This research aims to apply the tahfizh learning method in improving the quality of memorization for blind students at Raudlatul Makfufin Islamic Boarding School which includes planning for guidance on Al-Qur'an tahfizh learning methods for blind students, application of learning methods, results of guidance on Al-Qur'an tahfizh learning methods. This research used qualitative methods, with a case study approach design. To explore data, it requires observation, interviews, and documentation. Furthermore, these techniques were selected according to the research focus. The research results showed that the kinds of implementation of the tahfizh Al-Qur'an learning method improved the quality of memorization of blind students at Raudlatul Makfufin Islamic Boarding School. The tahfizh program at this Islamic boarding school is a mandatory program for all students, which aims to provide services to students in improving the quality of memorization of the Al-Qur'an. The findings indicated three tahfidz methods, namely Talaqqi, Tasmi, and Tikrar method. Raudlatul Makfufin Islamic Boarding School had implemented several methods previously, however, the results have not been able to provide a solution, because 27 (twenty-seven) students who achieved the memorization target, only 1 (one) person had memorized 3 Juz in one years. This issue supports the existence of the Talaqqi, Tasmi, and Tikrar methods to provide solutions to aspects of the tahfizh learning method for blind students. Based on the evaluation and supervision of tahfizh Al-Qur'an learning, it can significantly improve the quality and quantity of memorization for blind students, especially at the elementary level.